Representasi Dakwah dalam Novel Ayat-Ayat Cinta 2 Karya Habiburrahman El Shirazy - Galang Maheza (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Habiburrahman El Shirazy's novel entitled Ayat-Ayat Cinta 2, there are parts of the story that show a change in the attitude of the character who initially hated Islam to be positive towards Islam. This is of course due to the da'wah process which is not only through oral and written but also attitudes and actions that show good Islam. The purpose of this study was to determine the representation of da'wah in the novel AyatAyat Cinta 2 seen based on the storyline and characters, as well as the author's extrinsic element in representing da'wah in the novel. This research uses descriptive method using narrative analysis of Tzvetan Todorov and Algirdas Greimas, as the analysis knife. Furthermore it is known that most of the da'wah shown in this novel was carried out by Fahri. Fahri does all kinds of da'wah. Da'wah can be done by anyone and the person who does this da'wah is someone who knows and understands what should be done then invites others to do the same. The author's extrinsic element in representing da'wah in the novel Ayat-Ayat Cinta 2, namely, biography or rather the educational background, personal experience, and social conditions seen and experienced by the author.